EXPLOITING A BENEFIT OF COCONUT MILK SKIM IN COCONUT OIL PROCESS AS NATA DE COCO SUBSTRATE - Bambang Setiaji; Ani Setyopratiwi; Nahar Cahyandaru (Indonesian Journal of Chemistry, 2002)
A research to know influence of mixing concentration of coconut water and sucrose concentration to coconut milk skim as nata de coco substrate has been conducted. The variation was taken from mixing coconut water (0%, 25%, 35% and 50% and 100% as control) and the sucrose concentration (0.5%, 1%, 1.5% and 2%). Coconut milk skim boiled before used as substrat, yielded a coconut protein (blondo). The result of research showed that coconut milk skim can be used as nata de coco substrate with mixing coconut water and sucrose addition, mixing 50 % concentration coconut water representing optimum concentration. The content of crude fibre nata was yielded by higher concentration of sucrose, while mixing concentration coconut water do not influence crude fibre content.